Synthesis of Fe3O4@MIL-101-OH/Chitosan for adsorption and release of doxorubicin - Iman Najafipour; Nafiseh Emami; Pegah Sadeh; Adonis Amoli; Sareh Mosleh-Shirazi; Ali Mohammad Amani; Hesam Kamyab; Shreeshivadasan Chelliapan; Seyed Reza Kasaee; Ehsan Vafa (Polymer Testing)
This study reports the synthesis and characterization of a magnetic composite metal-organic framework, The Fe3O4@MIL-101-OH/Chitosan nanocomposite was used for the first time to adsorb and release the drug doxorubicin (DOX). The nanocomposite was characterized using scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), Brunauer-Emmett-Teller (BET), X-ray diffraction (XRD), and vibrating sample magnetometry (VSM). The characterization results showed that the synthesized nanocomposite has a crystalline structure and good magnetic properties. Also, this nanocomposite has a high specific surface area (610.36 m2/g). In this article, the effect of pH, contact time, and drug concentration on DOX adsorption were investigated, and the results showed that at optimal conditions, pH = 8, contact time = 90 min, and drug concentration is 350 ppm, the adsorption capacity of MIL-101-OH/Chitosan and Fe3O4@MIL-101-OH/Chitosan are equal to 185 and 174.3 mg/g. The adsorption data follows pseudo-second-order kinetic and Langmuir isotherm models. The adsorption was physical and reversible. As a result, drug release was checked. The Fe3O4@MIL-101-OH/Chitosan exhibited a controlled release over the period of 84 h at pH 5 and reached 80 % of the DOX release rate after 60 h. In conclusion, the Fe3O4@MIL-101-OH/Chitosan composite has great potential as a drug delivery system as a result of its high adsorption capacity and magnetic properties. This research provides a promising approach for the development of novel drug delivery systems for cancer therapy.